Penerapan Pengendalian Persediaan Menggunakan Metode Safety Stock dan Reorder Point untuk Meningkatkan Efisiensi Biaya Persediaan Barang Jadi: (Studi Kasus pada PT. Medal Queenindo) - Lutfhi Ramdani Fathurrohman; Nugraha, Arie Apriadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Inventory of finished goods is an important thing that must be maintained so that there are no excesses or shortages. Sales and profits of PT Medal Queenindo will decrease by almost 50% in 2022 due to weak inventory control and high cost of finished goods inventory. The purpose of this research is to apply the Safety Stock and Reorder Point methods to improve finished inventory cost efficiency using a quantitative descriptive method with a focus on the finished goods inventory method. The safety stock carried out by the company is by paying attention to sales in the last six months without regard to the number of items ordered. Meanwhile, the calculation is based on the formula put forward by M. Hudori, namely paying attention to the number of requests or existing orders. The Reorder Point made by the company only pays attention to the Total Forecast, Safety Stock and remaining stock. This obligation does not pay attention to the length of time for delivery there. Calculations based on the M.hudori formula pay attention to the average number of existing requests, Safety Stock, and the length of time for delivery after an order is placed.